The Interpersonal Antecedents of Attachment Security in Early Adulthood - Julie A. Blake; James G. Scott; Jake M. Najman; Hannah J. Thomas (Children)
Background/Objectives: The relevance of adult attachment security for physical and emotional wellbeing is increasingly evident. Developing a better understanding of the interpersonal antecedents of secure attachment in childhood and adolescence could enable opportunities for its promotion when attachment styles are more easily modifiable. Methods: Data from 3648 participants in a longitudinal birth cohort study were examined. At 21 years, participants completed the confidence (in self and others) subscale of the Attachment Style Questionnaire, a measure of attachment security. Path analysis was used to longitudinally examine the influence of maternal and child-reported interpersonal variables at birth, 5, and 14 years on attachment security in early adulthood. Results: Two pathways were identified. Firstly, child and family social relations at birth and 5 years predicted attachment security via the number of the child’s close friends at 14 years (β = 0.11, p < 0.001). Secondly, attuned caregiving at 14 years predicted attachment security via the recalled experiences of parental care up to 16 years, measured at 21 years (β = 0.28, p < 0.001). Greater adolescent family satisfaction directly predicted increased attachment security in early adulthood (β = 0.10, p < 0.001). Conclusions: Child and family social relationships from birth and throughout childhood and adolescence, along with attuned caregiving, led to increased attachment security in early adulthood. Public health and policy initiatives aimed at strengthening social support systems for caregivers and their children throughout childhood, and increasing the uptake of parenting programmes aimed at strengthening attuned caregiving, may lead to long-term improvements in the attachment security of offspring.